2021
DOI: 10.1093/jas/skab235.871
|View full text |Cite
|
Sign up to set email alerts
|

PSXIV-20 Ovine circulatory markers regulating the acute-phase response of variable stress responding sheep to LPS challenge

Abstract: Pathogens induce neuroendocrine-immune interactions in their hosts, which are a basis to overcome the microbial stressor. These interactions result in individual variation of the hypothalamic-pituitary-adrenal (HPA) axis response and could contribute to variable stress resiliency. In present study, a comprehensive set of circulatory markers was assessed in variable stress responding lambs selected from a population (n = 112) and categorized based on cortisol levels as high (HSR, 336.2 ±27.9 nmol/L, n =12), mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the same experimental design subjected to current study, Sohel et al [18] showed that a high-protein diet consumed by the mother predominantly changed the expression of mRNAs involved in myogenesis and immunity in the developing fetus's skeletal muscle. Both Shandilya et al [38] and Sharma et al [39,40] showed that sheep exposed to bacterial lipopolysaccharide challenge exhibited differentially regulated miRNAs such as miR-3957-5p, miR-329a-3p, miR-379-5p (Table 1) which regulate biological processes such as stress and immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…In the same experimental design subjected to current study, Sohel et al [18] showed that a high-protein diet consumed by the mother predominantly changed the expression of mRNAs involved in myogenesis and immunity in the developing fetus's skeletal muscle. Both Shandilya et al [38] and Sharma et al [39,40] showed that sheep exposed to bacterial lipopolysaccharide challenge exhibited differentially regulated miRNAs such as miR-3957-5p, miR-329a-3p, miR-379-5p (Table 1) which regulate biological processes such as stress and immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…In the same experimental design subjected to the current study, Sohel et al [ 18 ] showed that a high-protein diet consumed by the mother predominantly changed the expression of mRNAs involved in myogenesis and immunity in the developing fetus’s skeletal muscle. Both Shandilya et al [ 48 ] and Sharma et al [ 49 , 50 ] showed that sheep exposed to a bacterial lipopolysaccharide challenge exhibited differentially regulated miRNAs, such as miR-3957-5p, miR-329a-3p, and miR-379-5p ( Table 1 ) which regulate biological processes such as stress and immune responses.…”
Section: Discussionmentioning
confidence: 99%